Kinetic and equilibrium studies of decolorization of effluent of handmade paper industry by low-cost fly ash. Issue 53 (13th November 2016) - Agarwal, Saakshy; Yadav, Shashi; Sharma, Ashwini; Singh, Kailash; Gupta, A.B.
Abstract: Handmade paper is famous for its bright color made by single dye or admixture of dyes. Handmade paper industry emits colored effluent which requires cost-effective treatment technologies. In the scope of the present paper, studies have been conducted with a simulated dye solution having a mixture of dyes being used in the handmade paper industry. The original fly ash and adsorbed fly ash were characterized for SEM-EDX, XRD, and Fourier transform infrared (FTIR) studies. The FTIR studies of direct dyes used in mixture (direct orange, direct navy blue, and direct violet dye) were conducted. The batch studies were conducted with low-cost fly ash and various affecting parameters, i.e. pH, initial concentration, temperature of the dye solution, dosage, and particle size of fly ash. The maximum adsorption capacity of fly ash was found to be 120.48 mg/g with fly ash dosage of 40 g/L having particle size of 45–75 μm with dye solution at pH 2 and 40°C temperature. The better coefficient value of R 2 showed better fitting of the Langmuir isotherm with the experimental data. The kinetic sorption data are well represented by the pseudo-second-order kinetics for the entire sorption period. The change in enthalpy, entropy, and free energy were evaluated which indicated that the sorption process is endothermic, spontaneous, and feasible. The characteristics of the effluent of handmade paper industry after fly ash treatment in batch study confirm the acceptability of the use of fly ash for treatment of effluent of handmade paper industry.